ATP13A2 levels in serum and cerebrospinal fluid in patients with idiopathic Parkinson's disease. (July 2021) - Fernández-Espejo, Emilio; Rodriguez de Fonseca, Fernando; Suárez, Juan; González-Aparicio, Ramiro; Santurtún, Ana
Abstract: Background: The enzyme ATP13A2 holds promise as biomarker in Parkinson's disease (PD). No study has examined the content of ATP13A2 in serum and cerebrospinal fluid (CSF) in idiopathic PD cohorts, or how ATP13A2 relates to the clinical features of the disease. Methods: ATP13A2 concentration was evaluated with ELISA and immunoblotting. Correlations of serum and CSF ATP13A2 with clinical parameters were examined. The antiparkinsonian medication regimen was expressed as levodopa equivalent dose (LED, mg/day). Results: Serum ATP13A2 concentration was similar in patients and controls, and it correlated with LED and MDS-UPDRS part-IV score (p < .0001), a scale which allows evaluating motor complications. LED also correlated with MDS-UPDRS part-IV score (p < .0001). Serum ATP13A2 concentration and LED were higher in patients with motor complications than in patients without motor complications (p < .0001). The ratio of serum ATP13A2 concentration versus LED was calculated, and mean value was similar in patients with or without motor complications. ATP13A2 concentration in the CSF was undetectable in many subjects because the ELISA assay was hampered by its detection limit. Immunoblotting indicated that CSF ATP13A2 content was higher in patients relative to controls (p = .0002), and no clinical correlations were found. Conclusions: Increasing LED enhanced serum ATP13A2 concentration and facilitated the development of motor complications. There is a direct relationship between serum ATP13A2 level and the dose intensity of the antiparkinsonian dopaminergic medication. The associations between serum ATP13A2 and LED suggest that serum ATP13A2 content might be a marker of dopamine replacement therapy. HIGHLIGHTS: Serum ATP13A2 concentration is positively correlated with levodopa equivalent daily dose. Serum ATP13A2 concentration positively correlates with MDS-UPDRS part IV score. Serum ATP13A2 concentration is higher in patients with motor complications. The ratio of serum ATP13A2 concentration versus levodopa equivalent daily dose is similar in patients with or without motor complications. Serum ATP13A2 could be a marker of dopamine replacement therapy.